2021
DOI: 10.1002/adfm.202105297
|View full text |Cite
|
Sign up to set email alerts
|

Giant Photo‐Magneto‐Thermoelectric Effect of End‐On Oriented PEDOT Grown from Self‐Assembled 3D Tectons

Abstract: Conductive polymers (CPs) are arranged in the end-on direction on graphene surfaces using 3D tectons of ZnPc assemblies, to control carrier transport from hot to cold via external magnetic fields. Poly(3,4-ethylenedioxythiophene)s doped with tosylate are synthesized using monomer seeds that are complexed through pyridine units to 3D tectons on graphene via surface-confined hostguest chemistry, to provide an end-on-oriented polymer film on graphene with a high degree of crystallinity. The film shows free-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Synthesis of Clip (Figure S1a, Supporting Information): The synthesis of compounds 1 [9] and 2 [10] were previously described in the literature. Under an atmosphere of argon, 1 (1 g, 1.894 mmol) and t-BuOK (0.467 g, 4.735 mmol) were suspended in anhydrous THF (20 mL) and stirred 30 min at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of Clip (Figure S1a, Supporting Information): The synthesis of compounds 1 [9] and 2 [10] were previously described in the literature. Under an atmosphere of argon, 1 (1 g, 1.894 mmol) and t-BuOK (0.467 g, 4.735 mmol) were suspended in anhydrous THF (20 mL) and stirred 30 min at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…materials. [8,9] In particular, luminescent materials with ferroelectric properties could be developed as a material showing synergistic enhancement of luminescence and ferroelectricity (SELF) for a future display that provides a means of exchanging visual information and stimuli in all spaces including people and objects with self-energy harvesting capacity.…”
mentioning
confidence: 99%
“…In 2021, Kim et al reported similar phenomenon of the magneto-Seebeck effect in oriented PEDOT:TOS/graphene hybrid devices (Figure 15a,b). [99] Figure 15. a) Schematic drawing of the PEDOT:TOS-based photo-MTE device under a perpendicular magnetic field.…”
Section: Mte Devicesmentioning
confidence: 99%
“…After connecting six strips in series, the output power can reach 0.157 μW at a ΔT of 51.6 K, indicating that the film made by PEDOT nanowire has the potential to be employed in wearable devices. Moreover, controlled template-free in-situ polymerization of PEDOT was also studied to enhance the TE performance of the textile sublayer [199] . A simple one-bath template-free solution method was reported to fabricate PEDOT with an σ value of up to 560 S cm -1 and an S 2 σ value of 0.9 μW m -1 K -2 at room temperature.…”
Section: Pedotmentioning
confidence: 99%